2006
DOI: 10.1073/pnas.0605375103
|View full text |Cite
|
Sign up to set email alerts
|

A picornavirus protein interacts with Ran-GTPase and disrupts nucleocytoplasmic transport

Abstract: Active nucleocytoplasmic transport of protein and RNA in eukaryotes depends on the Ran-GTPase system to regulate cargoreceptor interactions. Several viruses, including the RNA picornaviruses, encode factors that alter nuclear transport with the aim of suppressing synthesis of antiviral factors and promoting viral replication. Picornaviruses in the cardiovirus genus express a unique 67-aa Leader protein (L), known to alter the subcellular distribution of IFN regulatory proteins targeted to the nucleus. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
146
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(153 citation statements)
references
References 34 publications
5
146
0
2
Order By: Relevance
“…If conformation plays a role in L M activity, outside of the zinc finger, it must be induced by the relevant binding partners. Indeed, when bound to Ran, L M 0P condensed and made specific contacts in the central hinge and acidic domains, via the same residues identified by mutagenesis (15,24). Surprisingly, however, the amino third of the protein, including the zinc finger, and both internal phosphorylation sites were left solvent exposed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If conformation plays a role in L M activity, outside of the zinc finger, it must be induced by the relevant binding partners. Indeed, when bound to Ran, L M 0P condensed and made specific contacts in the central hinge and acidic domains, via the same residues identified by mutagenesis (15,24). Surprisingly, however, the amino third of the protein, including the zinc finger, and both internal phosphorylation sites were left solvent exposed.…”
Section: Discussionmentioning
confidence: 99%
“…In cell-free assays with intact nuclei, within 5 min of the introduction of recombinant L E -GST (or GST-L E ), there is complete inhibition of all active import and export of host proteins and RNA through the nuclear pore complexes (NPCs) (24). The discovery that L E bound RanGTPase, the key regulator of nucleocytoplasmic trafficking (NCT), raised the initial possibility of putative stoichiometric inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of cardioviruses have focused attention on the L protein because of its multiple functions and importance in disease pathogenesis. In addition to its effect on apoptosis, cardiovirus L has been found to inhibit type I IFN transcription (13,23) and nucleocytoplasmic transport (which causes a block in mRNA egress the nucleus and therefore blocks host cell translation) (8,17). We recently found that although DA L and GDVII L both block type IFN transcription, they block at different steps in the IFNdependent IRF-3 pathway (23).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, EMCV L has been found to interfere with the apoptotic pathway downstream of caspase activation in EMCV infections of HeLa cells (18). The degree of apoptosis in different cell types may be related to the following: the timing of nonapoptotic lysis vis-à-vis apoptosis in a TMEV-infection, the interference by L of nucleocytoplasmic transport (8,17) in a particular cell type, and the absence of a component of an apoptotic pathway in a particular cell type following TMEV L expression. Fan et al found evidence of apoptosis in BHK-21 cells induced by BeAn L (9); however, this study examined only markers for apoptosis that are upstream of TUNEL staining.…”
Section: Discussionmentioning
confidence: 99%